Prototypes of heroes in the poems by Shakarim - Buteyev Б.О. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
July 11, 2023, marked the 165th anniversary of the talented Kazakh poet, writer, composer, philosopher-thinker, and scientist-historian Shakarim Kudaiberdiuly. It should be noted that since the rehabi litation of Shakarim Kudaiberdiuly, significant work has been carried out to study his work and activities. Despite the fact that a tremendous amount of work has been done among scientists, there are points that are worth focusing on and paying special attention to. In this article, the author for the first time analyzed the works of Shakarim. As a result of the research, it was possible to identify three historical characters who took place in the poet’s work. The poet used their names in the Kazakh spelling of that time: a gallant gentleman of Anglo-Saxon origin, acting as a prototype of the expression of the patronage of wealthy Kazakhs of the late 19th and early 20th centuries, Alfred Gwynne Vanderbilt I is known in his works as “Walder Beldet”. Hisham ibn Abdul-Malik, the Umayyad caliph, is known to Shakarim under the name “Asham patsa”, with whom the wise steppe man entered into an unequal dialogue, having put up a worthy resistance and emerged victorious. An Lushan is a nomadic diplomat who made the entire Tang Empire shudder, known to the poet as Pan-Zhi-Zan Khan. There are a number of personalities in Shakarim’s works, that require further clarification. This will be possible thanks to the study of other sources, that the poet used in his research.